FORMS OF ORGANIZATION OF INDEPENDENT EDUCATIONAL ACTIVITY OF STUDENTS OF HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTIONS - O.V. Malykhin (Academy of Cognitive and Natural Sciences, 2009)
Forms of organization of students' self-directed learning activities in higher pedagogical educational establishments are defined and theoretically backgrounded.